Newly Started Versus Previously Treated Statin Patients: A Retrospective Cohort Study Comparing Adherence and Persistence with Reference to Cardiovascular Prevention - Marta Martín-Fernández; M. Asunción González-González; M. Aránzazu Pedrosa-Naudín; Diego Fernández-Lázaro; F. Javier Álvarez; Eduardo Gutiérrez-Abejón (Pharmaceuticals)
Background/Objectives: Cardiovascular disease (CVD) remains the leading cause of death worldwide, and the effectiveness of statin therapy is critically dependent on patient adherence and persistence. The aim of this study was to evaluate adherence and persistence in newly started and previously treated statin patients, with reference to cardiovascular prevention. Methods: A retrospective cohort study was conducted to assess adherence and persistence in newly started and previously treated statin patients. Patients aged 18 years or older with a statin claim from 1 January 2021 to 31 December 2023 were included. Adherence was defined as a Medication Possession Rate (MPR) of 80% or greater. Persistence was defined as the time between the index date and treatment discontinuation. Binary logistic regression and Cox proportional hazard regression were used to analyze factors influencing adherence and persistence, respectively. Kaplan–Meier survival analysis was used to compare persistence between both cohorts. Results: Of the 411,956 patients on statins, 81.21% were adherent, with higher rates in the previously treated statin patients (83.05% vs. 73.73%; p = 0.001). Statin persistence decreased from 92.65% at 3 months to 78.28% at 12 months, with higher persistence rates in previously treated statin patients. Previously treated statin patients were more likely to be adherent (AOR: 1.29) and persistent (AHR: 2.08) than those newly started on statins. In secondary prevention patients, adherence was higher in the previously treated cohort (88.09% vs. 79.77%; p = 0.001) than in the newly started cohort (80.52% vs. 71.38%; p = 0.001). Similar results were observed for persistence; 82.97% vs. 81.65% (p = 0.001) and 65.08% vs. 61.57% (p = 0.001), respectively. Conclusions: Adherence and persistence to statins were higher in previously treated patients than in newly started patients, especially for secondary cardiovascular prevention. New strategies are needed to improve medication adherence and persistence in patients with poor cardiovascular prognosis.